ANALISIS YURIDIS TERHADAP AKIBAT HUKUM PUTUSAN PERNYATAAN PAILIT BAGI DEBITOR TERHADAP KREDITOR PEMEGANG HAK TANGGUNGAN - Umul Khair (JCH (Jurnal Cendekia Hukum), 2018)
The research and discussion of the problems as outlined in this scientific work is done with the aim of knowing which legal provisions apply to the creditors holding the Mortgage Rights in the case of the decree of declaration of bankruptcy, considering there are two different legal provisions, namely Bankruptcy Law Number 37 of 2004 and Insurance Rights Act No. 4 of 1996. This research is a Yuridi Normative research. Data obtained through literature research. The purpose of library research is to obtain secondary data. Primary data obtained through library research, then the data were analyzed qualitatively. From the result of the research, it is known that the Commercial Court judge in determining the decision of bankruptcy statement based its decision on the provisions of Law No. 34 of 2004, and the judges use legal principle of lex posteriori derogate legi priori to determine which legal provisions should be applied. Thus, both the bankrupt debtor and the creditor are subject to the provisions of bankruptcy, so that the holder of the mortg who has the position of the preferred creditor can only exercise his / her right of execution of the burden of the mortgage for a period of two months after a ninety-day suspension period since the bankruptcy decision was pronounced.